2019
DOI: 10.1016/s2095-3119(18)62010-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of trehalose in Pleurotus pulmonarius during heat stress response

Abstract: High temperature is one of the major abiotic stresses that limit edible mushroom growth and development. The understanding of physiological alterations in response to heat stress, and the corresponding mechanisms involved is vital for the breeding of heat-resistant edible mushroom strains. Although trehalose functions as a protectant against abiotic stresses in fungi, the putative role of trehalose in thermotolerance remains to be elucidated. In this study, we found heat stress inhibited the growth of two Pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 49 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Heat shock is an important adverse environmental stress that influences the growth and development of mushrooms. Therefore, understanding of physiological alterations in response to heat stress and the corresponding mechanisms involved is essential for the breeding of heat-resistance H. marmoreus strains (Liu et al 2019). Although, the heat shock response has been studied in considerable detail in yeast and plant (McAlister and Finkelstein 1980;Richter et al 2010;Song et al 2012), the mechanism of heat shock response in basidiomycetes remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock is an important adverse environmental stress that influences the growth and development of mushrooms. Therefore, understanding of physiological alterations in response to heat stress and the corresponding mechanisms involved is essential for the breeding of heat-resistance H. marmoreus strains (Liu et al 2019). Although, the heat shock response has been studied in considerable detail in yeast and plant (McAlister and Finkelstein 1980;Richter et al 2010;Song et al 2012), the mechanism of heat shock response in basidiomycetes remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the heat shock response has been studied in considerable detail in yeast and plant (McAlister and Finkelstein 1980;Richter et al 2010;Song et al 2012), the mechanism of heat shock response in basidiomycetes remains elusive. Mushrooms evolved various strategies to response and alleviate heat shock stress, including HSPs synthesis, trehalose accumulation, and reactive oxygen species scavenging (Chen et al 2017;Liu et al 2016Liu et al , 2018Liu et al , 2019Wang et al 2017). In this study, we focused on a HSPs gene involved in heat shock response in H. marmoreus.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, trehalose production is also important for fungi under temperature stress. Trehalose is known to be important in the acquisition of thermotolerance and desiccation tolerance in many fungal species (and much more widely across multiple groups of biota) (Everatt et al 2015;Gancedo & Flores 2004;Liu et al 2019;Tereshina 2005). In Saccharomyces cerevisiae, trehalose and intracellular water stabilise the membrane structure and other intracellular networks under temperature stress conditions (Piper 1993).…”
Section: Effect Of Temperature Stress On Metabolic Pathwaysmentioning
confidence: 99%
“…Increased level of trehalose is a response to stress conditions, such as high temperature, dehydration, oxidative stress and glucose starvation, for fungi (Kong et al, 2012b;Liu et al, 2016Liu et al, , 2019Zhao et al, 2018;Lei et al, 2019). Lei et al reported that the accumulated trehalose in P. ostreatus could promote the recovery growth after heat stress, and trehalose production was partly induced by ROS accumulation (Lei et al, 2019).…”
Section: Protein Related To Trehalose Metabolismmentioning
confidence: 99%
“…Heat treatment could also affect the intracellular and extracellular metabolites of mushroom mycelia, such as ganoderic acid and volatile components (Tereshina et al, 2011;Liu et al, 2018c;Zhang et al, 2019). To counteract the detrimental effects of heat, mushroom cells evolved multiple adaption systems by changing proteins expression including (1) heat stress signal responding transduction system (Guo et al, 2016;Loshchinina and Nikitina, 2016;Zhang et al, 2016;Liu et al, 2018b); (2) the induction of heat stress factors and heat shock proteins (HSPs) (Lee et al, 2006;Kurahashi et al, 2014;Zhang et al, 2016;Chen et al, 2017;Wang et al, 2018a); (3) ROS burst and significant antioxidant accumulations (Chen et al, 2017;Wang et al, 2017;Liu et al, 2018c); (4) anabolism inhibition and catabolism activation, such as trehalose accumulation (Kong et al, 2012b;Liu et al, 2016Liu et al, , 2019Chen et al, 2017). Recently, the protection effect of antioxidant kojic acid in H. marmoreus mycelia damage was studied (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%